CLIMATIC INFLUENCES ON AEDES MOSQUITO LARVAE POPULATION - Madi, Malinda; Ahmad, Rohani; Azleen Mohd Kulaimi, Noor; Wan Mohamad Ali, Wan Najdah; Ismail, Suzilah; Lee, Han Lim (Malaysian Journal of Science, 2011)
The impact of climate on Aedes larval population was studied. Monitoring of population was done using ovitraps. Ovitrap provides a simple and convenient monitoring method for Aedes surveillance as the number of eggs laid in a standard trap within a specific time period give a relative measurement of the number of mosquito in the same area. Ovitraps were set outdoors in selected dengue prone areas in Desa Pandan, Kuala Lumpur for 66 weeks. Weather stations, consisting of a temperature and relative humidity data logger and an automated rain gauge were installed at key locations in the study site. Week-to-week variations of larval densities were correlated against variations in the individual climatic parameters. Results of the study showed that there was a close relationship between the heavy rainfall and the increased mosquito population in the study sites. The study showed that previous week rainfall plays a significant role in increasing the mosquito population. (Keywords: Dengue, Aedes aegypti, Aedes albopictus, climatic parameter.)